Pemantauan Perubahan Posisi Garis Pantai Patimban untuk Mendukung Perencanaan Kawasan Pesisir Berkelanjutan - Putra, Andika Permadi; Nurrohman, Andy Wibawa (UNIVERSITAS NEGERI MAKASSAR, 2025)
Shoreline monitoring in the Patimban Beach area is needed to understand the phenomenon of sedimentation and abrasion that affect development patterns in coastal areas. The method used to obtain shoreline change data is the Digital Analysis Shoreline System (DSAS), using shoreline position data for several different times. Existing shoreline data is obtained from processing Sentinel 2 satellite imagery that utilizes green and near-infrared channels to separate water bodies and land with the Normalized Difference Water Index (NDWI) algorithm. The results obtained from the DSAS method for Patimban Beach from 2020-2024 are the occurrence of coastal accretion and abrasion. In general, the acceleration of changes in Patimban Beach between 2020-2024 ranges from -35.54 meters per year. From the results of this calculation, it is hoped that it will be a reference for the sustainable development of the Patimban Beach area.AbstrakPemantauan garis Pantai di kawasan Pantai patimban diperlukan untuk memahami fenomena sedimentasi dan abrasi yang berpengaruh terhadap pola Pembangunan di akwasan pesisir. Metode yang digunakan untuk mendapatkan data perubahan garis Pantai adalah Digital Analysis Shoreline System (DSAS), dengan menggunakan data posisi garis Pantai untuk beberapa waktu yang berbeda. Data garis Pantai eksisiting didapatkan dari pengolahan citra satelit Sentinel 2 yang memanfaatkan kanal hijau dan infrared dekat untuk memisahkan badan air dan daratan dengan algoritma Normalized Difference Water Index (NDWI). Hasil yang didapatkan dari metode DSAS untuk Pantai Patimban dari tahun 2020-2024 adalah terjadinya akresi dan abrasi Pantai. Secara umum, percepatan perubahan Pantai Patimban antara tahun 2020-2024 berkisar antara -35.54 meter per tahun. Dari hasil penghitungan ini, diharapkan jadi acuan untuk Pembangunan kawasan Pantai Patimban yang berkelanjutan.